2020
DOI: 10.3390/su12051906
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Electric Vehicles in the Developing Countries: A Literature Review

Abstract: Electric mobility offers a low cost of travel along with energy and harmful emissions savings. Nevertheless, a comprehensive literature review is missing for the prospects of electric vehicles in developing countries. Such an overview would be instrumental for policymakers to understand the barriers and opportunities related to different types of electric vehicles (EVs). Considering the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, a systematic review was performed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 114 publications
2
81
0
2
Order By: Relevance
“…Yet a set of financial and technical barriers persists as high upfront investment costs in vehicles and infrastructure constraining the uptake of such private initiatives, combined with persisting interrogations on the capacity of EVs to provide similar uses, compared to current fossil fuel vehicles in terms of road conditions, carried weight, range and speeds. These findings on environmental and economic drivers, as well as financial and technical hurdles for transport electrification, are consistent with other studies on e-mobility in low-and middleincome countries [79], where affordability, total cost of ownership and performance are significant aspects [11,80,81]. Regardless of these barriers, start-ups remain the most active actors in the field of e-mobility transitions, quite universally across the urban contexts (with the exception of Tanzania, where start-ups are more active in rural areas).…”
Section: Discussionsupporting
confidence: 92%
“…Yet a set of financial and technical barriers persists as high upfront investment costs in vehicles and infrastructure constraining the uptake of such private initiatives, combined with persisting interrogations on the capacity of EVs to provide similar uses, compared to current fossil fuel vehicles in terms of road conditions, carried weight, range and speeds. These findings on environmental and economic drivers, as well as financial and technical hurdles for transport electrification, are consistent with other studies on e-mobility in low-and middleincome countries [79], where affordability, total cost of ownership and performance are significant aspects [11,80,81]. Regardless of these barriers, start-ups remain the most active actors in the field of e-mobility transitions, quite universally across the urban contexts (with the exception of Tanzania, where start-ups are more active in rural areas).…”
Section: Discussionsupporting
confidence: 92%
“…We consider several regulatory approaches that support ZEVs in addition to incentive-based approaches. Most of the ZEV literature focuses on four-wheelers for developed countries, though in some developing countries, electric two-wheeler vehicles in particular might be more appropriate and affordable 56 .…”
Section: Fuel-switching Regulations Can Lead the MIXmentioning
confidence: 99%
“…An effective alternative option is the reuse of batteries and it is found that the carbon emission reduction potential of reusing batteries is similar to moving from an oilbased vehicle to an EV [7]. In the global context, high infrastructure cost, anxiety on the resale market value, increase in demand for power generation, strong oil-base vehicle market and unit cost are some of the resistive forces for EVs in developing countries [8]. For instance, developing countries like Pakistan cannot transition directly from oil-based vehicles to battery EVs due to factors like charging infrastructure, load shedding of electricity and high cost of non-renewable energy [9].…”
Section: Introductionmentioning
confidence: 99%